Pengaruh Penerapan Model Pembelajaran Mind Mapping Berbasis Lesson Study Terhadap Pemahaman Konsep dan Motivasi Belajar Siswa - Mastan Mastan (Publikasi Indonesia, 2023)
The purpose of this study was to determine the effect of the application of learning model based on the Lesson Study to concept of mind map (Mind Mapping) understanding and student motivation. This study was conducted on September 2013 of the junior class VIII Negeri7 Tarakan. This research is a quasi-experiment with a population of VIII class and research take a 2 class for sample. The sampling technique using cluster random sampling. Data were analyzed using SPSS 16.0 for Window. Analysis using Independent sample t-test test. The results of the analysis of the effect of the application of mind map learning model (Mind Mapping) Lesson Study based on students' understanding of concepts obtained t 2.110 at a significance level of 0.05 and df = 68 values obtained ttabel2,000 means thitung>ttabel for student motivation and obtained thitung 3.679 in significance level of 0.05 and df = 68 values obtained ttabel2,000 means thitung>ttabel. Based on the analysis of data it can be concluded that there are significant application of mind map learning model (Mind Mapping) Lesson Study is based on the understanding of concepts and student motivation.